Kinetic study of total phenolic content from Piper betle Linn. leaves extract using subcritical water - Nur Lailatul Rahmah,; Siti Mazlina Mustapa Kamal,; Alifdalino Sulaiman,; Farah Saleena Taip,; Shamsul Izhar Siajam, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The green plant-based extraction of phenolic compounds is still challenging and attractive due to their benefit. The mechanism controlling of desorption rate of phenolic compounds, measured as total phenolic content (TPC), from Piper betle Linn. (PBL) leaves using subcritical water, and a one-site kinetic desorption model (first order) was studied. One-site kinetic desorption model has well explained the extraction mechanism of phenolic compounds from PBL leaves using subcritical water through desorption and diffusion mechanism. This model fits with the experimental data and presents a good description of the extraction mechanism with R-squared of 0.94. The recovery of TPC from PBL leaves using subcritical water was influenced by intraparticle diffusion, temperature, and extraction time. The desorption rate constant in the one-site kinetic desorption model increased from 100 to 200 °C (0.3975±0.02 to 3.3045±0.00 min-1)and then decreased to 250 °C (3.2093±0.00 min-1). The highest TPC was recovered quickly for 5 min at 200 °C. Inaddition, a high yield of TPC was also obtained at a slow desorption process for 30 min at a lower temperature of 175°C. The low activation energy for the diffusion of phenolic compounds from PBL leaves of this study was 8.964 kJ/mol.This result showed that the one-site kinetic desorption model of subcritical water extraction has an excellent opportunityto be applicable in phenolic compounds recovery from PBL leaves. The one-site kinetic desorption rate constant andmathematical kinetic model equation achieved in this study might control the quality of phenolic compounds extractedfrom PBL leaves through subcritical water.